Casual Employment in Australia: The Influence of Employment Contract on Financial Wellbeing and Job Satisfaction - Buchler, Sandra (My University, 2007)
Over the last twenty years the level of casual employment, a form of non-standard employment, has risen substantially from 15.8% of the Australian labour force in 1984 to 27.3% in 2002. This represents a vast increase in a form of peripheral employment that denies employees the majority of benefits associated with paid employment, other than the right to one hour of pay for one hour of work. Given the current industrial relations climate, and the introduction of the new Federal Workplace Relations Amendment, casual employment is likely to be an increasingly prominent feature of the Australian labour market, establishing this as an important area of enquiry. This thesis will examine differences between casual and permanent employees using both objective and subjective measures of financial strain, financial satisfaction and job satisfaction. The analysis is carried out on Wave 1 of the Household Income and Labour Dynamics in Australia (HILDA) survey conducted in 2001. Results show that casual employees are more likely to be in ‘low status’ groups, tend to be more disadvantaged in the labour market and have higher levels of financial strain and lower levels of financial and job satisfaction. These findings suggest that people who are already marginalized in the labour market are also more likely to be working under a casual contract, a form of employment that is associated with high levels of financial strain and low levels of financial and job satisfaction.
Keywords: Employment; Labour market; Employment; Employment and unemployment